Formulation and Evaluation of Catfish ( Calias Sp ) Albumin Extract Ointment with Variations of Basis - Erik Risnawan; Davit Nugraha (LPPM STIKes Muhammadiyah Ciamis, 2023)
Catfish (Clarias sp) contains albumin which is an important protein needed by the human body, especially in the process of healing diseases. Giving this catfish extract functions as a nutrient, it is hoped that this nutrition can improve nutrition, increase the immune system and speed up the wound healing process or post surgery. This research is an experimental research, in which the albumin ointment formulation of catfish (clarias sp) extract was carried out, with variations of vaselin flavum and adeps lanae ointment bases in three formulations namely formulation 1, formulation 2 and formulation 3. The results of catfish extract (clarias sp) were then formulated in the form of an ointment. Then an evaluation of physical properties was carried out including organoleptic evaluation, homogeneity test, spreadability test, adhesion test, pH test. The results showed that the albumin extract ointment for catfish (Clarias sp) with variations in ointment base made a difference to the evaluation of albumin extract for catfish (Clarias sp) which included organoleptic tests (soft shape, white to yellow), homogeneity test (has round particles, irregular, no foreign particles), spreadability test (FI, 5.16cm: FII, 5.23cm: FIII, 5.06cm), adhesion test (FI, 3.19 seconds, FII 2.27 seconds, FIII 3.24 seconds), pH test (FI 6, FII 6, FIII 6). The conclusion that the vaseline flavum ointment combined with adeps lanae from catfish albumin extract meets the quality consists of an evaluation. homogeneity test, organoleptic test, adhesion test, spreadability test and pH test.